(untitled) (Vegueta: Anuario de la Facultad de Geografía e Historia, 2019)
Los investigadores han señalado diferentes lugares y épocas para el origen de las inscripciones líbico-bereberes canarias. En este trabajo se analizan las hipótesis más relevantes, además de señalar regiones que han sido poco estudiadas hasta la actualidad. Algunos signos canarios hallados en estas zonas deben ampliar por tanto el ámbito posible para realizar estudios comparativos. Researchers have indicated different times and places for the origin of Libyco-Berber inscriptions in the Canary Islands. This paper discusses the most important hypotheses, as well as pointing to regions that have been little studied up to the present day. Some Canarian signs found in these regions should therefore extend the possible area under discussion, so as to further realize comparative studies.